2021
DOI: 10.1186/s40538-021-00221-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving salinity tolerance in Salvia officinalis L. by foliar application of salicylic acid

Abstract: Background Higher absorption and translocation of sodium (Na) and chlorine (Cl) ions in plant tissue can lead to serious physiological and biochemical changes. However, salicylic acid (SA) is a natural signaling molecule responsible for the induction of environmental stress tolerance in plants. Spraying SA could provide protection against several types of stress such as salinity. This study aimed to show the influence of SA spraying (0.5 and 1 mM) on the damaging effects of NaCl toxicity (150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…Salt stress is an important environmental constraint that can affect the growth and productivity of wheat [ 3 , 6 ]. Previous studies have shown that the exogenous application of SA or MT enhances plant salt tolerance [ 7 , 9 , 10 , 16 ]. However, our knowledge regarding the mechanisms involved in their combined treatment-mediated salt tolerance still remains fragmentary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salt stress is an important environmental constraint that can affect the growth and productivity of wheat [ 3 , 6 ]. Previous studies have shown that the exogenous application of SA or MT enhances plant salt tolerance [ 7 , 9 , 10 , 16 ]. However, our knowledge regarding the mechanisms involved in their combined treatment-mediated salt tolerance still remains fragmentary.…”
Section: Discussionmentioning
confidence: 99%
“…Salicylic acid (SA, 2-hydroxybenzoic acid), as a plant growth regulator, can stimulate several biochemical events, resulting in a new metabolic state [ 7 , 16 ]. It has been shown that SA regulates plant salt tolerance by involving in redox homeostasis, suggesting that SA can interact with ROS signal pathways [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yadegari [26] showed that at low concentrations, while SA had a stimulating effect at higher concentrations, it reduced essential oil content in S. officinalis. Furthermore, Es-sbihi et al [27] also reported that a low (0.5 mM) SA application to S. officinalis reduced plant Na + content, improved growth, and increased nutrient (calcium, potassium, and phosphorus) levels, chlorophyll, essential oil content, and peltate gland density. SO plants are clearly highly tuned to the absolute levels of SA because a small amount of change can result in drastically different responses.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of manool, labdane type diterpene, at high salinity levels can be exploited as a precursor of ambergris fragrant products ( Taarit et al, 2010 ), but the severity of salt stress affects the physiological traits and yield, thus this can be considered more as a marker of severe salt stress in S. offciinalis . Alleviation of salt stress in sage has been confirmed after foliar application of SA with a variety of changes in the chemical composition of essential oils ( Zohra Es-Sbihi et al, 2021 ). Sage essential oil from aerial plant parts is mainly composed of 1,8-cineole, α/β-thujone, and camphor, and salt stress can induce a significant increase in these compounds with some new compounds recorded, such as viridiflorol, β-caryophyllene, myrentol, and pulegone.…”
Section: Salvia Officinalis Lmentioning
confidence: 97%